Studi Penelusuran Tingkat Adopsi Teknologi Peningkatan Produksi dan Kualitas Tanaman Salak - Rachmiwati Yusuf (Jurnal Sagu, 2008)
Investigation study of adoption level was evaluated from activities to increase product and quality of snake fruit plant conducted by BPTP Riau until 1998. These activities were evaluatedin April to September 2005. The aim of the evaluation was to obtain data on adoption level of recommended technology, and impacts of recommended technology on productivity and farmer income. During evaluation, some information such as farmer income was collected by survey method. Result indicated that score from evaluation of activities to increase product and quality of snake fruit plant averaged 2,04 which was moderate for cooperator farmer, while score for non cooperator farmer, while score for non cooperator farmer averaged 1,69.